2011
DOI: 10.1063/1.3621429
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic study of nanotwins in NiTi shape memory alloys

Abstract: Atomistic simulations are performed to study the structure and geometrical limit of nanoscale twins in NiTi shape memory alloys. We analyze compound twins as narrow as $1 nm, involving a few atomic layers. A novel nanotwinned structure is found, forming through the martensitic transformation of sublattices. We predict the temperatures of phase transformation, which are consistent with experimental measurements. The results provide an atomistic basis for further study of nanometer length scale effects on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 58 publications
9
81
0
Order By: Relevance
“…Of course, the martensite phase fraction used in the constitutive model is obtained from the present study, noting that in [74] it is assumed that the thermally induced martensite phase fraction varies linearly with temperature. However, as demonstrated herein, based on experimental studies [43], phase field simulations [31,33,34] and molecular dynamics simulations [25,27] the martensite phase fraction varies exponentially with temperature. The total free energy is expressed as a function of the total martensite phase fraction, thus the dependency of the phase fraction on temperature does not influence the free energy and thermodynamics laws [74].…”
Section: Figure-5mentioning
confidence: 62%
See 2 more Smart Citations
“…Of course, the martensite phase fraction used in the constitutive model is obtained from the present study, noting that in [74] it is assumed that the thermally induced martensite phase fraction varies linearly with temperature. However, as demonstrated herein, based on experimental studies [43], phase field simulations [31,33,34] and molecular dynamics simulations [25,27] the martensite phase fraction varies exponentially with temperature. The total free energy is expressed as a function of the total martensite phase fraction, thus the dependency of the phase fraction on temperature does not influence the free energy and thermodynamics laws [74].…”
Section: Figure-5mentioning
confidence: 62%
“…This difference is mainly due to size effects and consideration of the single crystal (in the simulations) vs. the polycrystalline (in the experiment) NiTi SMA samples; this is addressed in detail in the following sections. Significant size effects have been reported extensively, [25,27,28,30,61] where it is also demonstrated that the presence of defects such as free surfaces can appreciably alter the martensite transformation start Size effects are demonstrated in Figure 3 and some relevant results (evolution of microstructure at different temperatures and sizes) are documented in the supplementary material. Figure 3 shows the variation of martensite phase fraction with respect to temperature for different size of NiTi films.…”
Section: Figure-2mentioning
confidence: 82%
See 1 more Smart Citation
“…The study by Wu et al [20] showed that dislocation nucleation started from surfaces during torsional deformation of NiTi nanowires. The study by Zhong et al [13,21] showed that complex phase transformation behaviour including the super-elasticity and the shape memory effects of NiTi nanostructures was observed during compressive loading and unloading. Tomohiro et al [22] studied the microscopic mechanism of stress-induced martensitic transformation of NiTi alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports claimed that the stress-induced martensite transformation would occur accompanied with deformation twinning when the alloy was subjected to plastic deformation in the austenite state [18]. Zhong et al performed an in-depth study on the structure and geometrical limit of nanoscale twins in NiTi by combining the crystallographic theory with atomistic simulations [19]. However, the role of atomic interactions involved during structural transformations, such as twinning and size effect as well as the temperature-dependent behavior, is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%